Modification of Soil Hydroscopic and Chemical Properties Caused by Four Recent California, USA Megafires - Vera Samburova; Eric Schneider; Christopher P. Rüger; Shelby Inouye; Brad Sion; Kevin Axelrod; Palina Bahdanovich; Lukas Friederici; Yasaman Raeofy; Markus Berli; Alexandra Lutz; Ralf Zimmermann; et al. (Fire, 2023)
While it is well known that wildfires can greatly contribute to soil water repellency by changing soil chemical composition, the mechanisms of these changes are still poorly understood. In the past decade, the number, size, and intensity of wildfires have greatly increased in the western USA. Recent megafires in California (i.e., the Dixie, Beckwourth Complex, Caldor, and Mosquito fires) provided us with an opportunity to characterize pre- and post-fire soils and to study the effects of fires on soil water repellency, soil organic constituents, and connections between the two. Water drop penetration time (WDPT) tests performed in the field showed a significant increase (from <1 s up to >600 s) in WDPT from pre- to post-fire soils. This increase in soil water repellency after fires was confirmed by increases in apparent contact angle (ACA) between 1.1 and 9 times from unburned to burned soils. The chemical characterization of burned soils with high resolution mass spectrometry showed the increased abundance of hydrophobic organics (e.g., PAH-like compounds and organic molecules with a low number of oxygen atoms) as well as the correlation of the average H/C ratio and aromaticity index (AI) with ACA. Most likely, these compounds contribute to post-fire soil water repellency that triggers hydrological effects such as landslides, flooding, and debris flows.